2014
DOI: 10.14411/eje.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on population growth and life table parameters of Nephus arcuatus (Coleoptera: Coccinellidae)

Abstract: The development, reproduction and life table parameters of the predator Nephus arcuatus Kapur (Coleoptera: Coccinellidae), the most important predator of the spherical mealybug, Nipaecoccus viridis (Newstead) (Homoptera: Pseudococcidae) were studied at five constant temperatures (15, 20, 25, 30 and 35 ± 1°C, 65 ± 5% RH and a photoperiod of 14L : 10D). The duration of total pre-adult stage was found to decrease with increase in temperature from 60.0 days at 20°C to 15.3 days at 35°C. The oviposition period last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Thus, mass rearing of N. arcuatus on either N. viridis or P. citri should not change the prey selection of the predator once released in the field, enabling N. arcuatus to feed successively on different mealybug species without reducing its predation potential. These findings combined with the results of Zarghami et al (2014) showed that N. arcuatus can successfully survive and reproduce in temperatures of around 30°C and indicate that N. arcuatus could make an important contribution to the control of mealybugs in warm regions.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Thus, mass rearing of N. arcuatus on either N. viridis or P. citri should not change the prey selection of the predator once released in the field, enabling N. arcuatus to feed successively on different mealybug species without reducing its predation potential. These findings combined with the results of Zarghami et al (2014) showed that N. arcuatus can successfully survive and reproduce in temperatures of around 30°C and indicate that N. arcuatus could make an important contribution to the control of mealybugs in warm regions.…”
Section: Discussionsupporting
confidence: 54%
“…Kaur and Virk (2012) observed that the adults of C. montrouzieri, the key competitor in controlling mealybugs, consumed 1613.81 first instars and 73.4 adult females of P. solenopsis in their lifetime when held at a temperature of 27°C (longevity of male: 68.30 days; longevity of female: 61.78 days). Mustu and Klincer (2013) reported that the adults of Nephus kreissli Fürsch and Uygun consumed 23.5 eggs of Planococcus ficus Signoret in 24 h. Zarghami et al (2014) reported the longevity of male and female N. arcuatus held at 30°C to be 116.5 days and 86.1 days, respectively. Our experiment was performed in a 24-hour period (less than that of Kaur and Virk (2012)), yet based on the results and the greater longevity of N. arcuatus, this predator could be more efficient in controlling mealybugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This small coccinellid occurs widely and abundantly in citrus orchards in Dezful, southwestern Iran (personal observation). Recent investigations on the biology and consumption capacity of this predator confirm its potential for the control of N. viridis in the citrus orchards [11,12]. However, more studies are needed to develop this predator within a successful biological management programme.…”
Section: Introductionmentioning
confidence: 99%